2017
DOI: 10.1007/s11060-017-2612-8
|View full text |Cite
|
Sign up to set email alerts
|

Skin toxicities associated with tumor treating fields: case based review

Abstract: The novel anti-mitotic based tumor treating fields (TTFields) is FDA approved for recurrent glioblastoma. Recently the phase III upfront trial combining the Novo TTF-100A device, called Optune, with temozolomide following concurrent radiation therapy and chemotherapy, demonstrated improvement in survival. Wider use of this novel therapy is expected. The most common adverse event is dermatologic, which dominates compared to the next most frequently observed adverse event of headaches, the incidence of which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Therefore, longer treatment breaks should be avoided to allow optimal clinical outcome. Nevertheless, there are circumstances that inevitably lead to discontinuation of the therapy, e.g., skin irritations 32,33 . It would be of clinical importance to determine if such treatment breaks could be bypassed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, longer treatment breaks should be avoided to allow optimal clinical outcome. Nevertheless, there are circumstances that inevitably lead to discontinuation of the therapy, e.g., skin irritations 32,33 . It would be of clinical importance to determine if such treatment breaks could be bypassed.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis compiling 6 randomized controlled trials combining BEV with TMZ for ndGBM indicated a 33% reduction in the risk of disease progression with no effect on OS (20). Anti-angiogenic therapies such as BEV may further increase the risk of skin-related AEs associated with TTFields (21). Concurrent therapies for ndGBM with TTFields that may exacerbate skin irritation underscore the necessity of effective prophylactic strategies to minimize the occurrence of skin toxicities associated TTFields (e.g., proper shaving techniques, scalp cleansing, and array relocation) as well as AE specific treatment-based strategies (e.g., topical or oral antibiotics, isolation of affected skin, or topical corticosteroids) to manage skin irritation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors increase the risk of developing dermatologic AEs in patients treated with TTFields (39). Prior craniotomies, especially those that necessitated scalp reconstruction, may increase risk (39,41), and skin breakdown is more likely to occur from transducer array placement over surgical scar lines and surgical hardware from craniotomy repair. While surgical hardware is not an absolute contraindication for TTFields use, oncologists should consider this when planning array placement, and oncology nurses should discuss array and adhesive placement and avoidance of surgical hardware and scars with patients and caregivers.…”
Section: Management Of Dermatologic Adverse Events Identification Andmentioning
confidence: 99%
“…• Return to clinic in 2 weeks; if condition persists, consider oral antibiotic/treatment break scalp to injury from the arrays (41). Radiation injury may also render skin less likely to recover from the subclinical alterations related to array placement, continued contact, and removal.…”
Section: Management Of Dermatologic Adverse Events Identification Andmentioning
confidence: 99%